1992
DOI: 10.1111/j.1476-5381.1992.tb09051.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐activating factor (PAF) plays an important role in the immediate asthmatic response in guinea‐pig by augmenting the response to histamine

Abstract: 1 To investigate the role of platelet activating factor (PAF) in the immediate asthmatic response, we examined the bronchial reactivity to histamine after administration of PAF to guinea-pigs or antigen challenge to passively sensitized guinea-pigs. 2 A bolus injection of PAF (20-40ngkg-1), which did not cause a significant increase in intrathoracic pressure (ITP), augmented the bronchial response to histamine almost 8 fold. This airway hyperreactivity was observed even 1 min after PAF treatment. 3 A subthresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
(26 reference statements)
3
7
0
Order By: Relevance
“…In this regard, our data clearly demonstrate that the phospholipid mediator PAF is intimately involved in the regulation of leukotriene and cytokine synthesis, and as was described by Morooka et al (40) in histamine release.…”
Section: Discussionsupporting
confidence: 69%
“…In this regard, our data clearly demonstrate that the phospholipid mediator PAF is intimately involved in the regulation of leukotriene and cytokine synthesis, and as was described by Morooka et al (40) in histamine release.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, autocrine and paracrine regulatory mechanisms have been described among these mediators (30)(31)(32)(33)(34). The phospholipid mediator PAF is intimately involved in this regulatory network (29,35). The molecular mechanisms by which PAF exerts its autocrine effects are still not completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…ACh induced by inhalation of bacterial lipopolysaccharide in guinea-pigs (Arimura et al, 1993) is similar to that required for the inhibition of IgGI-mediated bronchoconstriction. Morooka et al (1991) have demonstrated that the doses of a platelet-activating factor (PAF) antagonist required to suppressed antigen-induced airway hyperreactivity were more than 100 times higher than the dose required to inhibit PAF-induced responses. These findings lead to the Acetylcholine (A.g kg-', i.v.)…”
Section: Ige-mediated Bronchoconstrictionmentioning
confidence: 99%